MODEL PENGEMBANGAN PERGURUAN TINGGI ISLAM BERBASIS KULTURAL DI JAWA TIMUR (Studi Kasus Tentang Pengelolaan Pesantren di UIN Malang dan ISID Gontor Ponorogo) - Miftahul Huda, dkk (lp2m-uin malang, 2006)
Lately, many people appraise that Islamic Colleges, both state and private, have failed in developing their vision and mission to produce intellectual students. Even, they also believe that Islamic Colleges have lost their base cultural character and become the “westernization agent” of their students. However, there are still many dauntless Islamic Colleges that use “cultural” as their trade mark. The aim of this research is to explain the management of boarding school in Islamic College viewed from its objective, its structural relationship with the college and also its activities and moral values. Using symbolic of phenomenological-interaction approach, the research shows that there are varied methods of boarding school management that are aimed to support the college in educating the students from the aspects of intellectual, moral, spiritual, and language ability. It is also found that there are two models of relationship between boarding school and college. First, college considered as a boarding school back up, like in ISID Gontor. And second, boarding school considered as college back up, like in UIN Malang.The activities in boarding school are varied and have to be done by all students, this kind of activity comes from central command, however, there are also local activities managed by the students that are done by some students only.The moral values developed in boarding school are: spiritual, moral, professional, sincerity, autonomy, simplicity, Islamic fraternity, and freedom.Kata Kunci: PTAI, Pesantren Kampus, Islam Kultural